2009
DOI: 10.1007/s11104-009-9924-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant–rhizobia mutualism influences aphid abundance on soybean

Abstract: The mutualism between legumes and nitrogen-fixing soil bacteria (rhizobia) is a key feature of many ecological and agricultural systems, yet little is known about how this relationship affects aboveground interactions between plants and herbivores. We investigated the effects of the rhizobia mutualism on the abundance of a specialized legume herbivore on soybean plants. In a field experiment, soybean aphid (Aphis glycines) abundances were measured on plants (Glycine max) that were either (1) treated with a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 57 publications
1
56
0
2
Order By: Relevance
“…They showed that mostly positive effects of rhizobia on caterpillar performance did not occur in a cyanogenic legume strain, suggesting that the symbiosis between legumes and rhizobia may be an important driver of herbivore infestation, legume performance and thus plant community productivity. However, and similar to the uncertainty mentioned for AMF effects, the level of plant resistance to herbivores may differ between rhizobia strains (Dean et al 2009). …”
Section: Rhizobiamentioning
confidence: 84%
See 1 more Smart Citation
“…They showed that mostly positive effects of rhizobia on caterpillar performance did not occur in a cyanogenic legume strain, suggesting that the symbiosis between legumes and rhizobia may be an important driver of herbivore infestation, legume performance and thus plant community productivity. However, and similar to the uncertainty mentioned for AMF effects, the level of plant resistance to herbivores may differ between rhizobia strains (Dean et al 2009). …”
Section: Rhizobiamentioning
confidence: 84%
“…In addition to affecting plant growth, the association with rhizobia may increase plant resistance against herbivores (Mathesius 2003;Dean et al 2009). The recent study by Kempel et al (2009) showed that N provided by rhizobia may be used for the production of N-based plant defence compounds.…”
Section: Rhizobiamentioning
confidence: 99%
“…It also implies that host-mediated effects of Rhizobium on aphids depend on the composition of microbial communities the legume symbiont interacts with in the rhizosphere (Whipps, 2001;Bais et al, 2006;Raaijmakers et al, 2009); as microbial communities that exist in cattle manure culture (Chachkhiani et al, 2004;Maeda et al, 2010), are unlikely to be similar to those in Effective Microbes ® (Naluyange et al, 2014). Increase in aphid populations due to Rhizobium inoculation has also been reported in soybean and in the commercial Rosecoco bean (Dean et al, 2009;Naluyange et al, 2014 Danielsen, S., Boa, E., Mafabi, M., Mutebi, E., Reeder, R., Kabeere, F., & Karyeija, R. (2013). Using plant clinic registers to assess the quality of diagnoses and advice given to farmers: a case study from Uganda.…”
Section: Inmentioning
confidence: 98%
“…For example, root colonization by Rhizobium has been found to promote plant resistance to insect pests (Thamer et al, 2011). However, Rhizobium colonization of roots has also been related to an increase in aphid and fungal incidences on leguminous shoots, which has been attributed to improved nutritive suitability of the host plant due to nitrogen fixation (Dean et al, 2009(Dean et al, , 2014Naluyange et al, 2014). Such effects of Rhizobium on legumes are modified by soil fertility amendments (El-Wakeil & El-Sebai, 2009;Dean et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation